USING ARDUINO IN THE LABORATORY WORK "STUDY OF THE CONNECTION OF BIPOLAR TRANSISTORS AND THEIR AMPLIFIER CHARACTERISTICS" (Scientific journal of the Fergana State University, 2024)
This article will look at ways to connect bipolar transistors to circuits as switches and learn how to amplify them and test them using arduino. In radio electronics, bipolar transistors are widely used as signal amplification and electronic switches. The purpose of the article is to organize the laboratory work "Study of the connection of bipolar transistors and their amplification characteristics" in the approved curriculum for the bachelor's degree in physics of higher education and to analyze its convenience.